The Role of Gonadotropin-Releasing Hormone in Cancer Cell Proliferation and Metastasis - Gründker, Carsten; Emons, Günter (Frontiers in Endocrinology, 2017)
Expression of GnRH and its receptor as a part of an autocrine regulatory system of cell proliferation has been demonstrated in a number of human malignant tumors of the urogenital tract, including cancers of the ovary, endometrium, urinary bladder, and prostate. In addition, in breast cancers and in some cancers of non-reproductive tissues, including pancreatic cancers and glioblastoma, GnRH receptor expression was found. Dose- and time-dependent antiproliferative effects of GnRH agonists in cell lines derived from these cancers have been observed by various investigators. GnRH antagonists also have marked antiproliferative activity in most cancer cell lines tested, indicating that the dichotomy of GnRH agonists and antagonists might not apply to the GnRH system in cancer cells. The classical GnRH receptor signal-transduction mechanisms, known to operate in the pituitary, are not involved in the mediation of antiproliferative effects of GnRH analogs in cancer cells. Rather, the GnRH receptor interacts with the mitogenic signal transduction of growth factor receptors and related oncogene products associated with tyrosine kinase activity, via activation of a phosphotyrosine phosphatase (PTP), resulting in downregulation of cancer cell proliferation. In addition, GnRH-induced PTP-activation inhibits G-protein coupled estrogen receptor 1 (GPER), a membrane-bound receptor for estrogens, playing an important role in breast cancers lacking expression of estrogen receptor α (ERα). Furthermore, cell invasion in vitro, metastasis in vivo and increased expression of S100A4 and CYR61 - factors playing important roles in epithelial-mesenchymal-transition (EMT), invasion and metastasis - are downregulated by GnRH in metastatic breast, ovarian, and endometrial cancer cells. This review will summarize the present knowledge of the GnRH receptor and its signaling in human cancers.